A Reassessment of Ibn ‘Abbās’s Inheritance Views and Their Contemporary Legal Relevance in Indonesia - Adam Wahid Pangaji; Faishal Agil Al Munawar (PT. Riset Press International, 2026)
This study reassesses the inheritance views of Ibn ʿAbbās and examines their contemporary legal relevance for the reform of Islamic family law in Indonesia. The application of inheritance provisions under the Compilation of Islamic Law (KHI) remains varied, with some Religious Court judges adhering to the jumhūr al-fuqahāʾ while others draw upon the perspectives of scholars such as Ibn ʿAbbās, Ibn Ḥazm, and Hazairin. Recent Supreme Court jurisprudence has introduced progressive reforms that gradually shift Indonesian inheritance law toward a bilateral framework grounded in principles of justice, gender equality, and legal pluralism. Central to these developments is Ibn ʿAbbās’s interpretation of walad in Qur’an 4:176 as encompassing both sons and daughters, thereby excluding the inheritance rights of the decedent’s siblings when a daughter exists. Because his inheritance views are dispersed across classical tafsīr and fiqh literature, this library-based study systematically reconstructs and analyzes four key areas in which Ibn ʿAbbās diverges from the jumhūr: the gharāwāin, daughters excluding siblings, ʿawl, and inheritance involving a grandfather alongside siblings. The findings demonstrate that Ibn ʿAbbās’s insights not only align with several aspects of Supreme Court jurisprudence but also contribute to ongoing legislative efforts, including the Draft Law on Islamic Inheritance, which adopts his position on the gharāwāin. Nevertheless, certain issues particularly inheritance between a grandfather and siblings remain unregulated in Indonesian law. This reassessment shows that Ibn ʿAbbās’s minority opinions possess substantial contemporary relevance and offer constructive contributions to the future reform of Islamic family law in Indonesia.